1966
DOI: 10.1139/p66-066
|View full text |Cite
|
Sign up to set email alerts
|

The Hall and Seebeck Effects in Nonstoichiometric Bismuth Telluride

Abstract: Detailed measurements of electrical conductivity ( a ) , Hall coefficient ( R H ) , and Seebeck coefficient ( a ) were made on seven bismuth telluride samples of composition Bi?Tea+,, with x ranging from -0.06 to $0.48. Above room temperature the slope of R=T3I2 gave a n apparent energy gap about 50% higher than that from the a slope, and the Hall mobility decreased steeply with a T-4 dependence. These effects could be explained by a n electron-to-hole mobility ratio (b) near unity, but the magnitude of a a t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 12 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…The cross section of the ribbon is set to be s = 10nm× 0.5 nm. The mobility is µ * = 2000cm 2 V −1 s −1 , taken from the bulk mobility at 80K [18]. For the phonon thermal conductivity we assumed κ L = 0.1Wm −1 K −1 estimated from the bulk values [19,20].…”
Section: Competition Between Edge and Bulk Transportmentioning
confidence: 99%
“…The cross section of the ribbon is set to be s = 10nm× 0.5 nm. The mobility is µ * = 2000cm 2 V −1 s −1 , taken from the bulk mobility at 80K [18]. For the phonon thermal conductivity we assumed κ L = 0.1Wm −1 K −1 estimated from the bulk values [19,20].…”
Section: Competition Between Edge and Bulk Transportmentioning
confidence: 99%
“…The temperature dependence of the electron (hole) mobility is given by the relation µ e ≈ T −1.7 (µ h ≈ T −2.0 ) [11,30,31]. Using the mass components listed above, we estimate the electron and hole density-of-state effective mass…”
Section: Evaluation Criteria Of a Quantum Size Effect In The Bismumentioning
confidence: 99%
“…These studies were mainly carried out on bulk samples [1], but no much work has been reported on thin films of Bi 2 Te3 . So far very few measurements of the optical properties have been reported [2,3].…”
Section: Introductionmentioning
confidence: 99%